A Case for Diaspora Voting Rights in Nigeria - Christopher Ochanja Ngara & Ganiyu L. Ejalonibu (UIR Press, 2022)
This paper makes a case for diaspora voting rights in Nigeria. Using desk research method, the paper noted that diaspora voting rights is an essential ingredient of an inclusive representative democracy and consistent with global best practices. It observes that whereas many countries in Africa have adopted one form of diaspora voting or the other, Nigeria, the largest democracy in Africa, is yet to adopt same despite the notable contributions of Nigerians diaspora community to national development. The paper stressed that while the rights to vote home government is protected under various international statutes and conventions, the activation of these rights in Nigeria has remained elusive due to the provisions in Sections 77(2) and 117(2) of the 1999 Constitution as well as Section 13(1) (c) of the Electoral (Amendment) Act 2010. The paper recommends the amendment of these provisions to expressly provide for diaspora voting Nigeria.